Financial Literacy and Fintech Use’s Effects on Indonesian Young Adults’ Financial Well-Being: Financial Behavior as a Mediation Variable - Utami , Nevi Margi; Pradana , Mahir; Hidayat , Agus Maolana (Journal of Ecohumanism, 2025)
Using financial behavior as a mediating variable, this study examines the relationship between financial literacy and fintech use and financial well-being in Indonesia’s emerging adult population. In order to test this study, 444 respondents who fit the criteria for the emerging adulthood age group completed an online questionnaire.The study’s findings indicate that financial literacy has a negligible and detrimental impact on financial well-being; however, if financial behavior acts as an indirect mediator, the effects will be substantial and favorable.Fintech use also makes a substantial contribution to the enhancement of financial well-being, particularly through the direct and indirect mediation of financial behavior. These findings provide practical recommendations for the government, financial institutions or fintech and emerging adulthood service providers to improve Financial Literacy, build awareness of the wise use of fintech, and emphasize the importance of having positive financial behavior among the young generation in Indonesia, in order to achieve financial well-being that is expected in the future.